Steamship RELIANCE and (possibly) Steamship HANNAH at dock at Tanana, ca. 1907 - Nowell, Frank H., 1864-1950 (1907)
Caption on image: 6110 On verso of image: Tanana Tanana is located at the junction of the Yukon and Tanana Rivers and had long been a Native American trading locality before the coming of the Europeans. In 1880, the Alaska Commercial Company trading post was established near here. St. James Episcopal Mission was established here in 1891, and about 1897, one mile downstream from the mission, the trading post of the Northern Commercial Company was established. (pg. 947) Notes from Donald Orth, Dictionary of Alaska Place Names: Geological Survey Professional Paper 567 (Washington: United States Government Printing Office, 1967) The HANNAH was owned by the Northern Navigation Company, a subsidiary of the Northern Commercial Company. The sternwheel passenger and freight steamer RELIANCE was built by the Northern Navigation Company at St. Michael in 1907. (pg. 112 and pg 140 ). [Notes from Gordon Newell, ed., The H.W. McCurdy Marine History of the Pacific Northwest (Seattle: Superior Publishing Co., 1966)] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number